2012
DOI: 10.1111/tpj.12010
|View full text |Cite
|
Sign up to set email alerts
|

The WOX13 homeobox gene promotes replum formation in the Arabidopsis thaliana fruit

Abstract: SUMMARYThe Arabidopsis fruit forms a seedpod that develops from the fertilized gynoecium. It is mainly comprised of an ovary in which three distinct tissues can be differentiated: the valves, the valve margins and the replum. Separation of cells at the valve margin allows for the valves to detach from the replum and thus dispersal of the seeds. Valves and valve margins are located in lateral positions whereas the replum is positioned medially and retains meristematic properties resembling the shoot apical meri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 88 publications
(182 reference statements)
4
71
0
1
Order By: Relevance
“…FUL expression was slightly increased in rpl-2 mutants (Fig. 4B), consistent with the repression of a valve factor by a replum factor (Romera-Branchat et al, 2013). However, FUL expression was decreased in rpl-2 ntt-3D mutants, indicating that ntt-3D suppressed the effect of rpl mutation.…”
Section: Resultssupporting
confidence: 48%
“…FUL expression was slightly increased in rpl-2 mutants (Fig. 4B), consistent with the repression of a valve factor by a replum factor (Romera-Branchat et al, 2013). However, FUL expression was decreased in rpl-2 ntt-3D mutants, indicating that ntt-3D suppressed the effect of rpl mutation.…”
Section: Resultssupporting
confidence: 48%
“…WOX5 is an auxin-inducible gene expressed in the quiescent center of the root meristem and in its direct precursor cells during the early globular stage of embryogenesis (Haecker et al, 2004;Gonzali et al, 2005). WOX8 is expressed in the egg cell and zygote, whereas WOX13 is expressed during primary and lateral root initiation and development, in the gynecium, and during embryo development (Deveaux et al, 2008;Romera-Branchat et al, 2012). The sequential reactivation of WOX13, WOX5, and then WOX8 suggests that these genes are also regulators of cell division during PdC culture.…”
Section: Discussionmentioning
confidence: 99%
“…WOX13 OG might be a good candidate to study the functional diversification of WOX genes (Chandler et al 2008). The WOX13 subfamily genes were proposed to be involved in replum development, lateral root formation, and vegetative to floral growth transition (Chandler et al 2008;Romera-Branchat et al 2012). Romera-Branchat et al (2012) found that WOX13 expressed mainly in the meristematic tissue in Arabidopsis (RomeraBranchat et al 2012).…”
Section: Communicated By Sureshkumar Balasubramanianmentioning
confidence: 98%